La influencia de la música como factor sociocultural en la construcción de la identidad personal de las jóvenes estudiantes de los novenos años egb de la unidad educativa fiscomisional “la inmaculada” en la ciudad de Loja. Periodo 2018- 2019 - Medina Paccha, Andrea Stefania (2019)
The art, like a concept it’s the way in our society can communicate even the most abstractive of the feelings; also, is the right way to stablished relationships with others and with us. That’s the reason that makes the present research is about analyze the transcendence of the music like a society and cultural factor, to build the personal identity of the students in nine grade of the high school “Unidad Educativa Fiscomisional La Inmaculada” In the city of Loja. This research is support in the Corbin and Strauss theory that determinate in a systematic way about the human behavior and the social word with an empiric base; that hypothesis was not experimental because they didn’t use experimental variable. The experimental universe was conformed of: 128 nine grade students, five teachers (4 of them are the tutors of the classrooms and one is the teacher of the course named “Educacion Cultural y Artistica”) and also the director of the high school Sor Nila Gomez. The methods that I used in the present work were: scientific, analytic, synthetic, hermeneutics and inductive; also was used instruments of investigation like: interviews to the authorities and teachers to determinate the incidence of the music in the identities process in the students with the object of obtain information about their psychologic development, determinate their preferential patrons and music affinities. The results analysis let me evidence that the music is a relevant factor in the identity consolidation because it’s an element that allows the exteriorization of the feelings and the stablished of social connections that was involved in the social affective development of the person making possible the appreciation and compression of the reality.